PSVI-33 Performance and meat quality of castrated and intact Santa Inês lambs slaughtered at different stages. (7th December 2018) - Ribeiro, E; Fernandes, F; Constantino, C; Grandis, F; Giotto, F; Koritiaki, N; Castro, F
Abstract: The objective of this study was to evaluate the performance and meat characteristics of castrated and intact Santa Inês male lambs slaughtered at three different thicknesses of subcutaneus fat. Thirty-four lambs, approximately 3 months of age, 19.37 ± 3.73 kg of body weight were used. Four weeks prior to the experiment, half of the animals were castrated. Lambs were further divided into three groups, according to the criteria for slaughter: fat thicknesses of 1, 3 and 6 mm; measured with an ultrasound equipment. All animals received the same diet. Criteria of 1 and 3 mm were achieved after 39 and 84 days in feedlot. As the criterion of 6 mm was not attained up to 130 days of confinement, lambs were slaughtered at that time, with 4 mm of fat thickness. Fat thickness measured with a caliper on the carcasses were 0.87, 3.11 and 3.60 mm. There were no interactions (P>0.05) between sexual conditions and slaughter criteria. Average daily gain was similar (P>0.05) among criteria (average of 0.267 ± 0.052 kg/day). However, final body weight (29.94 ± 2.03; 40.42 ± 2.67 and 53.85 ± 2.03 kg) and feed conversion (4.17 ± 0.39; 4.71 ± 0.43 and 6.01 ± 0.39) were different (P0.05) among criteria, panelists found that lambs slaughtered with 3.6 mm of fat thickness were less (P<0.05) desirable. Average daily gain (0.283 ± 0.013 vs 0.247 ± 0.012 kg) was greater (P<0.05) for intact than castrated lambs; however, the meat of intact lambs was less derirable. The other traits were similar for both sexual conditions. We can conclude by the performance and meat results that it is better to slaughter Santa Inês lambs with 3 mm of fat cover, and for the best acceptability of the meat the lambs shoud be castrated. Key Words: